Comparison of short-term clinical outcomes of intra-articular injection of micro-fragmented adipose tissue and stromal vascular fraction cells for knee osteoarthritis treatment: A retrospective single-center cohort study - Takuma Maeda; Satoshi Sobajima; Tomoyuki Matsumoto; Masanori Tsubosaka; Takehiko Matsushita; Hideki Iwaguro; Ryosuke Kuroda (Regenerative Therapy)
Background: Stromal vascular fraction (SVF) cells and micro-fragmented adipose tissue (MFAT) have potential for treating knee osteoarthritis (OA), but their efficacy has not been compared. This study aimed to compare the clinical outcomes of SVF and MFAT for knee OA. We hypothesized that SVF provides stronger short-term effects, while MFAT offers more sustained benefits. Methods: A retrospective single-center cohort study was conducted on patients with knee OA, with 36 SVF and 36 MFAT cases selected through propensity score matching between September 2017 and February 2022. Patients with KL grades I–IV varus knee OA, significant pain (VAS ≥40), and functional impairment despite conservative treatments were included. Those with knee trauma, severe bony defects, infections, genu valgus, osteonecrosis, rheumatoid arthritis, or severe deformities were excluded. Clinical outcomes were assessed using the visual analog scale, KOOS, knee range of motion, extension/flexion strength, and MRI T2 mapping. Results: SVF and MFAT groups demonstrated significant improvements in VAS (p < 0.01 for both groups). Both groups showed notable improvements in extension angle, extension/flexion muscle strength, and KOOS, with no significant differences between them. However, the MFAT group demonstrated significantly greater improvement in flexion angle compared to the SVF group (p = 0.03). No serious adverse events were reported. T2 mapping showed significant improvements in cartilage quality in both groups, with the MFAT group demonstrating superior improvements in specific lateral regions. Responder rate in SVF group initially improved but declined over time; however, the MFAT group showed sustained improvement from six months onward. Conclusion: T2 mapping revealed that MFAT had better cartilage preservation than that of SVF cells in less-loaded areas, with a potentially longer-lasting therapeutic effect. These findings offer important insights for clinicians to tailor treatment strategies based on patient needs and disease progression.